Reinforced Geopolymer Concrete after Exposure to Fire - Sarker, Prabir; McBeath, S. (Precast/Prestressed Concrete Institute, 2011)
Geopolymer is an alternative binder for concrete. Heat-cured fly ash based geopolymer concrete can be an ideal material for precast concrete members. This paper presents the residual strength of reinforced geopolymer concrete after exposure to fire. Ordinary Portland cement (OPC) and geopolymer concrete wall panels of 500 mm 500 mm (19.7 in 19.7 in) size and thickness of 125, 150 and 175 mm (4.9 in, 5.9 in and 6.9 in) were exposed to fire on one side up to 960 0C for two hours. The specimens were reinforced with a single layer of steel mesh. Compressive strengths of the geopolymer and OPC concrete varied in the range of 42 to 50 MPa (6 to7.3 ksi). The specimens were cooled down to normal temperature after exposure to fire and tested under concentric compressive load. The test failure loads were compared with the calculated failure loads of the original unheated specimens. The failure load of the geopolymer concrete members was in the range of 61 to 71% of the calculated original values. The range of the failure loads of OPC concrete members was 50 to 53% of the original strengths. Therefore, the geopolymer concrete specimens retained higher post-fire strengths as compared to the OPC concrete specimens.